Training On The Use Of The Institutional Repository For Librarians At The Mandalika Educational University Library UPT - Ridwan, Ridwan; Susilawati, Hirma; Putriana, Aluh; Ridha, Kinanti Ainun; Soadikin, Muhammad (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The Mandalika University of Education Library UPT currently has an institutional repository. The current condition is that the use of institutional repositories by librarians is not yet optimal, seen from the governance of the repository websites they own, especially the organization of content, apart from that the management is not in accordance with the national standards required by the Ministry of Education, Culture, Research and Technology (Kemendikbud) in terms of this is indexation to the Rama Repository. Considering the responsibility of the Mandalika University of Education Library UPT to help develop the institutional repository system and also improve current conditions, it is necessary to carry out activities in the form of training assistance, or assistance in using the institutional repository system. The methods used in this community service activity consist of lectures, discussions, mentoring and training on the use of the Mandalika University of Education Institutional Repository website. The results of this community service activity can be concluded that the training activity on the use of institutional repositories for librarians at the Mandalika Education University Library UPT had a positive impact and influence on the participants, in this case all librarians at the Mandalika Education University Library UPT (UNDIKMA).